2017
DOI: 10.1186/s40360-017-0152-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of enzyme-replacement-therapy with agalsidase alfa in 36 treatment-naïve Fabry disease patients

Abstract: BackgroundFabry disease (FD) is an X-linked lysosomal storage disorder resulting from the α-galactosidase A gene mutations. Enzyme-replacement-therapy (ERT) products for FD currently used include agalsidase alfa and agalsidase beta. There are many reports on efficacy and safety of ERT. However, most of the previous studies are done as a retrospective medical records analysis.MethodsThe Japan Fabry Research - 002 (JFR-002) was a prospective observational clinical study of 36 ERT-naïve FD patients (14 men and 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…An S1P receptor antagonist [FTY720 (fingolimod)] and a humanized monoclonal S1P antibody (LT1009) are available and they might represent a means to deplete S1P levels in patients with NPHS14 [ 10 , 20 , 21 ]. In addition, SGPL1 enzyme replacement therapy may be a potential therapeutic intervention, similar to the one used for Gaucher disease and Fabry disease [ 22 , 23 ].…”
Section: Treatmentmentioning
confidence: 99%
“…An S1P receptor antagonist [FTY720 (fingolimod)] and a humanized monoclonal S1P antibody (LT1009) are available and they might represent a means to deplete S1P levels in patients with NPHS14 [ 10 , 20 , 21 ]. In addition, SGPL1 enzyme replacement therapy may be a potential therapeutic intervention, similar to the one used for Gaucher disease and Fabry disease [ 22 , 23 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In the phase III ATT RAC T study, migalastat is a treatment option for ERTexperienced patients [18]. No racial differences have been reported with regard to Fabry disease, and its clinical phenotypes are likely similar among races [2,6,22]. Therefore, it is meaningful that this subanalysis of Japanese patients showed that the efficacy of migalastat was not affected by race; there were also no unexpected safety concerns.…”
Section: Discussionmentioning
confidence: 91%
“…Enzyme replacement therapy (ERT) with agalsidase alfa or agalsidase beta is the mainstay of treatment [5]. Results of previous clinical studies have shown efficacy and good tolerability of ERT in some Japanese patients with Fabry disease [6,7]. However, several challenges remain, including infusion-associated reactions, reduced quality of life associated with lifelong parenteral treatment, and the decrease in efficacy after development of circulating antibodies to the enzyme [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy and safety of enzyme replacement therapy (ERT) with agalsidase alfa or agalsidase beta have been confirmed. Five years of treatment with ERT resulted in regression of LVH and an improvement in myocardial function in subgroups of patients [3], thus preventing these patients from experiencing cardiac function decline [4] in two previous studies. However, the long-term effects of ERT on cardiac dysfunction in Fabry disease are not clearly understood.…”
Section: Introductionmentioning
confidence: 93%